1996
DOI: 10.1159/000282816
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study between Etiological Factors of Calcium Oxalate Monohydrate and Calcium Oxalate Dihydrate Urolithiasis

Abstract: A comparative study between different etiological factors of calcium oxalate monohydrate (COM) and calcium oxalate dihydrate (COD) is presented. The most frequent alteration in COD urolithiasis was associated with hypercalciuria, whereas in COM urolithiasis was associated with urinary pH. A comparison between COM and COD groups of stone formers that exhibited 1 2 or 3 alterations was performed. Thus, in individuals with two simultaneous alterations, the association between altered urinary pH and hypomagnesiuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
4
8
0
Order By: Relevance
“…These biochemical findings corresponded to previous studies [6,10] which demonstrated that practically 100% of urine meeting such conditions belonged to stone-formers. Predicted results using To correlate and establish a simple relationship among the measured biochemical parameters in a system with reduced dimensionality, a principal component analysis (PCA) was performed including calcium, phosphate, magnesium and phytate urinary concentrations in the analysis.…”
Section: ) ×supporting
confidence: 91%
See 1 more Smart Citation
“…These biochemical findings corresponded to previous studies [6,10] which demonstrated that practically 100% of urine meeting such conditions belonged to stone-formers. Predicted results using To correlate and establish a simple relationship among the measured biochemical parameters in a system with reduced dimensionality, a principal component analysis (PCA) was performed including calcium, phosphate, magnesium and phytate urinary concentrations in the analysis.…”
Section: ) ×supporting
confidence: 91%
“…Volume and biochemical cut-offs of 12 h abnormal urinary lithogenic risk parameters, in accordance with authors' experience and literature data[6,10].…”
supporting
confidence: 74%
“…Thus, several clinical studies have been undertaken in stone‐formers with the aim of correlating urine composition with the occurrence of COM and COD in their calculi, to estimate the force required to achieve complete stone disruption and clearance during lithotripsy, or to predict the likelihood of stone recurrences. A strong relationship has been reported to occur between COD stones and hypercalciuria [1,4–7], reduced citrate levels [1,7] and higher pH [5]. On the other hand, COM calculi occur more frequently in association with normocalciuria [8].…”
Section: Introductionmentioning
confidence: 99%
“…The calcium oxalate dihydrate renal calculi usually generate in individuals with abnormally high urinary excretion of calcium and/or oxalate (hypercalciuria and/or hyperoxaluria) [33]. The calcium oxalate dihydrate renal calculi appear confined in cavities of low urodynamic efficacy.…”
Section: Calcium Oxalate Dihydrate Renal Calculimentioning
confidence: 99%